A method for preparing a titanium-based composite material with high strength and toughness and 700°C service performance

By introducing a variety of reinforcement bodies into the titanium-based composite material and forming a mesh-like basket-like tissue, the problem of insufficient performance of existing materials under room temperature and high temperature conditions is solved, and high strength and toughness and service performance of 700°C are achieved.

CN117966052BActive Publication Date: 2025-03-07HARBIN INST OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410208928.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-26
Publication Date
2025-03-07
Estimated Expiration
2044-02-26

AI Technical Summary

Technical Problem

The existing high-temperature titanium-based composite materials have shortcomings in room temperature strength and high-temperature service performance, especially in high-temperature conditions above 650℃, making it difficult to take into account both room temperature strong plasticity and high-temperature resistance.

Method used

By designing a multi-layered and multi-effect material structure, different sizes of reinforcement bodies, such as TiB whiskers, Y2O3, La2O3, Si, etc., through in-situ self-reaction and hot extrusion technology, a net-like basket-like tissue is formed to improve the overall performance of the material.

Benefits of technology

A titanium-based composite material with high strength and high toughness at room temperature and 700℃ is realized. The tensile strength of room temperature is greater than 1300MPa, the elongation is greater than 7%, and the tensile strength of 650MPa, and the elongation is greater than 20%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117966052B_ABST
    Figure CN117966052B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a titanium-based composite material with both high strength and toughness and 700°C service performance, comprising the following steps: step 1, according to the designed content of the reinforcing phase, calculate the content of each reinforcing powder in the added powder M in the raw material powder to determine the mass ratio of the TC25G alloy powder and each reinforcing powder; step 2, weigh the TC25G alloy powder and the added powder according to the designed mass ratio, and perform ball milling to mix the powders so that the powders are evenly mixed to obtain a composite powder; step 3, hot press sintering the obtained composite powder, and perform in-situ autogenous reaction to obtain a bulk composite material; step 4, hot extruding the obtained bulk composite material to obtain a titanium-based composite material with both room temperature strong plasticity and serviceability. The titanium-based composite material of the present invention significantly improves its high temperature performance above 700°C while ensuring that it has excellent room temperature strength-plasticity / toughness matching. The titanium-based composite material of the present invention can be used in aerospace vehicles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a titanium-based composite material with high strength and toughness and 700°C service performance, belonging to the technical field of titanium alloys and composite materials thereof. Background Art

[0002] In order to meet the dual demands of future aerospace vehicles for structural weight reduction and performance improvement, especially the urgent demand for high toughness and high temperature service performance of key lightweight structural components at room temperature and high temperature conditions. As a key material for modern aircraft engines, high-temperature titanium alloys are widely used in aircraft engine blades, disks, casings and other components to reduce engine weight and improve the thrust-to-weight ratio of aircraft, thereby significantly improving the service performance of aircraft engines. However, with the increase in the operating temperature of aircraft, higher requirements are placed on the service performance of high-temperature titanium alloys. At the same time, the service conditions of aircraft have become more complex, and the service performance requirements of high-temperature titanium alloys are no longer limited to a single performance indicator, but are expected to have excellent comprehensive performance at room temperature and high temperature conditions.

[0003] In order to further improve the comprehensive performance of titanium alloys, the current research focus is mainly on improving the high-temperature strength of materials through composite methods. However, there are some problems with titanium-based composite materials in the past, such as the single type of reinforcing phase and the neglect of the design and regulation of the microstructure of the matrix titanium alloy. Therefore, the commercial high-temperature titanium alloys currently developed on the market are relatively insufficient in terms of room temperature strength, and there is still an inversion problem of room temperature strength-plasticity / toughness. More importantly, these materials have insufficient performance under high temperature conditions above 650°C. There is an urgent need to develop a new type of titanium alloy and its composite materials with a service temperature above 700°C and excellent room temperature strength and plasticity. Summary of the invention

[0004] The present invention aims to solve the bottleneck problem that it is difficult to achieve both room temperature strength and plasticity matching and high temperature strength improvement in existing high temperature titanium-based composite material research, and further proposes a method for preparing a titanium-based composite material with both high strength and toughness and 700°C service performance.

[0005] The technical solution adopted by the present invention to solve the above problems is: the present invention comprises the following steps:

[0006] Step 1: Calculate the content of each strengthening powder in the added powder M in the raw material powder according to the designed strengthening phase content to determine the mass ratio of the TC25G alloy powder and each strengthening powder;

[0007] Step 2: Weigh the TC25G alloy powder and the external powder according to the designed mass ratio, and mix them by ball milling to make the powders evenly mixed to obtain composite powder;

[0008] Step 3, hot pressing and sintering the obtained composite powder, and performing an in-situ autogenous reaction to prepare a bulk composite material;

[0009] Step 4: hot-extrude the obtained block composite material to obtain a titanium-based composite material with both room temperature strength and plasticity and serviceability.

[0010] Furthermore, the added powder in step 1 includes original β grain boundary strengthening powder, α / β phase boundary strengthening powder and matrix strengthening powder.

[0011] Furthermore, the mass fraction of the original β grain boundary strengthening powder in the composite powder is 0.05-5%, the original β grain boundary strengthening powder includes at least one of B powder, TiB2 powder, Y powder and La powder, and the particle size of the original β grain boundary strengthening powder is 0.05-10μm.

[0012] Furthermore, in step 3, at least one reinforcing phase of TiB, Y2O3 and La2O3 is generated at the original β grain boundary through the in-situ autogenous reaction.

[0013] Furthermore, the mass fraction of the α / β phase boundary strengthening powder in the composite powder is 0.05-3%; the α / β phase boundary strengthening powder includes Si powder, and the particle size of the α / β phase boundary strengthening powder is 0.05-5 μm.

[0014] Furthermore, in step 3, at least one reinforcing phase of (Ti,Zr)5Si3 and (Ti,Zr)6Si3 is generated at the α / β phase interface through the in-situ autogenous reaction, and the size of the reinforcing phase is 0.01-5μm.

[0015] Furthermore, the mass fraction of the matrix strengthening powder in the composite powder is 0.05-5%, the matrix strengthening powder includes at least one of Ta powder, Mo powder and W powder, and the particle size of the matrix strengthening powder is 0.01-5 μm.

[0016] Further, in step 2, the nominal composition of the TC25G alloy powder is

[0017] Ti-6.5Al-4Zr-2Sn-4Mo-1W-0.2Si, and the particle size of the TC25G alloy spherical powder is 10-300 μm.

[0018] Furthermore, the matrix structure of the titanium-based composite material obtained by step 4 is a basket-like structure composed of α phase and β phase; wherein the α phase is lamellar, including micron-scale primary α phase and nanometer-scale secondary α phase; the β phase is separated by the interwoven α phase. The primary α phase lamella length is 1-50 μm and the width is 0.5-3 μm; the secondary α phase lamella length is 0.05-2 μm and the width is 10-200 nm.

[0019] Furthermore, the tensile strength σ of the titanium-based composite material obtained in step 4 at room temperature is b Greater than 1300Mpa, elongation δ greater than 7%; tensile strength σ at 700℃ b Greater than 650MPa, elongation δ greater than 20%

[0020] The beneficial effects of the present invention are:

[0021] 1. The matrix selected in the present invention is TC25G dual-phase titanium alloy, which has multiple advantages, including high temperature resistance, high strength, high toughness, and heat treatment strengthening. Compared with near-α-type high-temperature titanium alloys, TC25G has greater potential in organizational regulation and performance improvement due to its high content of β-stabilizing elements. The alloy can be used for a long time at a temperature of up to 550°C, providing a reliable performance foundation for applications in high-temperature environments.

[0022] 2. The present invention is based on the concept of "multi-effect response". It introduces reinforcements of different sizes into the material and places them at different positions of the material to bear the load, so as to achieve multi-level and multi-effect material response. Specific measures include the introduction of TiB whiskers, which effectively limits the size of the original grains; the introduction of rare earth oxides Y2O3 or La2O3, which effectively reduces the oxygen content in the powder metallurgy process; the introduction of fast eutectoid Si elements, which effectively strengthens the matrix phase interface; the introduction of high melting point Ta, Mo or W elements, which play a role in solid solution strengthening and improve the heat resistance of the matrix. These elements jointly promote the improvement of the strength and plasticity of the composite material through the coupling effect of multiple elements. This design concept comprehensively improves the performance of the composite material through the synergistic effects of multiple effects, and achieves an optimized response to material properties at different levels.

[0023] 3. The preparation method adopted by the present invention is simple, stable and highly controllable, and the type and content of the reinforcing phase are regulated by powder metallurgy technology. At the same time, by introducing the second phase at the high-temperature weak zone-phase interface in the alloy, a multi-level and multi-scale reinforcing phase distribution is formed, thereby improving the high-temperature strength of the interface.

[0024] 4. The present invention realizes a multi-level and multi-scale basket-like structure by regulating the matrix organization. This organizational structure shows excellent strength-plasticity matching at room temperature and high temperature conditions, and realizes a complex and orderly weaving of the internal structure of the material, so that it can take into account both strength and plasticity at room temperature and high temperature environments, and at the same time has high fracture resistance and creep resistance, so that it meets the design requirements for room temperature strength-plasticity matching and high temperature resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a flow chart of a method for preparing a titanium-based composite material having both high strength and toughness and 700°C service performance according to the present invention;

[0026] Figure 2 is a scanning electron microscope image of the titanium-based composite material prepared in Example 1;

[0027] Figure 3 is a tensile property curve diagram of the titanium-based composite material prepared in Example 1 at room temperature and 700°C;

[0028] Figure 4 is a scanning electron microscope image of the titanium-based composite material prepared in Example 2;

[0029] Figure 5 is a tensile property curve diagram of the titanium-based composite material prepared in Example 2 at room temperature and 700°C;

[0030] Figure 6 is a scanning electron microscope image of the titanium-based composite material prepared in Example 3;

[0031] Figure 7 It is a tensile property curve diagram of the titanium-based composite material prepared in Example 3 at room temperature and 700°C.

[0032] Figure 8 It is a comparison diagram of the tensile property curves of the titanium-based composite materials prepared in Examples 1 to 3 at room temperature and at 700°C. Specific embodiments

[0033] The present invention can be further understood by the following specific examples of the present invention, but they are not intended to limit the present invention.

[0034] Embodiment 1:

[0035] like Figure 1 As shown, in a specific embodiment of the present invention, a method for preparing a titanium-based composite material having both high strength and toughness and 700°C service performance comprises the following specific steps:

[0036] Step 1: According to the designed content of reinforcing phase or reinforcing element, the calculated mass ratio of TC25G alloy powder and additional powder M is as follows. The additional powder M is classified into original β grain boundary strengthening powder, α / β phase boundary strengthening powder and matrix strengthening powder according to the role played.

[0037] The original β grain boundary strengthening powder includes TiB2 powder and Y powder (i.e., yttrium powder), and the mass fraction of the original β grain boundary strengthening powder in the composite powder is 5%; the particle size of the original β grain boundary strengthening powder is 0.05-10 μm;

[0038] The α / β phase boundary strengthening powder includes Si powder, and the mass fraction of the α / β phase boundary strengthening powder in the composite powder is 1%; the particle size of the α / β phase boundary strengthening powder is 0.05-5 μm;

[0039] The matrix reinforcement powder includes W powder, and the mass fraction of the matrix reinforcement powder in the composite powder is 0.05%; the particle size of the matrix reinforcement powder is 0.01-5 μm.

[0040] Step 2: Weigh TC25G alloy (also the matrix alloy) powder and the added powder M according to the designed mass ratio, and mix them by ball milling to make the powders evenly mixed to obtain composite powder.

[0041] Among them, the nominal composition of the TC25G titanium alloy powder used is Ti-6.5Al-4Zr-2Sn-4Mo-1W-0.2Si, and the particle size of the TC25G alloy spherical powder is 10-300μm.

[0042] During the ball milling mixing, the rotation speed of the ball mill is 250 r / min, the ball milling time is 5 h, the ball-to-material ratio is 4:1, and the ball milling atmosphere is Ar gas.

[0043] Step 3: hot-pressing and sintering the obtained composite powder in a vacuum-sealed container, and performing an in-situ autogenous reaction to prepare a bulk composite material. The original β grain boundary, α / β phase interface, matrix composition and organization of the matrix alloy are enhanced by the in-situ autogenous reaction.

[0044] The added TiB2 powder generates TiB whiskers at the original β grain boundaries through an in-situ autogenous reaction. The TiB whiskers generated by the reaction are short rod-shaped or needle-shaped, with a length of 1-50μm and a width of 0.1-5μm. The TiB whiskers play a role in bearing loads and improve the strength of the material at room temperature and high temperature. At the same time, TiB, as a nucleation site for the α phase, can significantly refine the matrix grains, avoid the appearance of coarse Widmanstatten structure, and improve the strength and plasticity of the material.

[0045] The added Y powder reacts with O at the original β grain boundary to form a stable high melting point compound Y2O3. The Y2O3 generated by the reaction is in granular form with a size of 0.05-10μm. Y2O3 is dispersed in the matrix alloy, playing a role of dispersion strengthening, which is beneficial to improving the high temperature instantaneous strength and endurance strength of the matrix alloy. In addition, the reduction of O content in the matrix and the interface solves the problem of powder metallurgy brittleness and improves the plasticity of the material.

[0046] The added Si powder generates at least one of the reinforcing phases (Ti, Zr) 5Si3 and (Ti, Zr) 6Si3 at the α / β phase interface through an in-situ autogenous reaction, and is distributed at the α and β phase interfaces. The reinforcement generated by the reaction is in the form of submicron particles with a size of 0.01-5μm. The dispersed silicide can bear the load and effectively hinder the dislocation movement, thereby improving the high temperature strength and creep resistance of the titanium alloy.

[0047] The strengthening of the matrix mainly comes from the effect of the added element W (i.e., strengthening element) on the material composition and organization. The added element W is dissolved in the matrix crystal at the atomic scale to exert a strengthening and toughening effect, thereby improving the high-temperature softening resistance of the matrix titanium alloy. The effect on composition refers to the high-melting-point W element being dissolved in the lattice, which, on the one hand, exerts a solid solution strengthening effect, and on the other hand, improves the stability of the material at high temperatures. Organizational strengthening refers to the control of the matrix with a multi-scale microstructure through thermal deformation.

[0048] In the hot pressing sintering, the hot pressing sintering temperature is 1300° C., the hot pressing sintering pressure is 30 MPa, and the sintering time is 1 hour.

[0049] Step 4: hot-extrude the obtained bulk composite material to regulate the matrix structure, further refine the grains, and obtain a titanium-based composite material (also a multi-scale matrix structure) with excellent room temperature strength and plasticity and service performance above 700°C.

[0050] like Figure 2 As shown, the matrix structure is a basket-like structure formed by the α phase and the β phase. The α phase is lamellar, including a micron-sized primary α phase and a nanometer-sized secondary α phase, and the β phase is separated by the interwoven α phases. The primary α phase lamella length is 1-50 μm and the width is 0.5-3 μm; the secondary α phase lamella length is 0.05-2 μm and the width is 10-200 nm.

[0051] TiB whiskers are arranged linearly along the extrusion direction at the interface of the original matrix ball after deformation (i.e. after hot extrusion treatment), and are distributed in a network shape perpendicular to the extrusion direction. Y2O3 particles are distributed at the interface of the original matrix ball after deformation (i.e. after hot extrusion treatment).

[0052] During hot extrusion, the block material is kept warm in a box-type heat treatment furnace for 30 minutes, the holding temperature is 1000°C, the extrusion die is kept warm at 300°C, and the extrusion ratio is 13:1.

[0053] like Figure 3 As shown in the figure, the titanium-based composite material with both room temperature strength, plasticity and serviceability prepared by the above steps has a tensile strength σ at room temperature b 1310Mpa, elongation δ is 8.8%; tensile strength σ at 700℃ b The tensile strength is 712 MPa and the elongation δ is 22%.

[0054] Embodiment 2:

[0055] like Figure 1 As shown, in a specific embodiment of the present invention, a method for preparing a titanium-based composite material having both high strength and toughness and 700°C service performance comprises the following specific steps:

[0056] Step 1: According to the content of the designed reinforcing phase or reinforcing element, the mass ratio of the TC25G alloy powder and the additional powder M is calculated as follows. The additional powder M is classified into original β grain boundary strengthening powder, α / β phase boundary strengthening powder and matrix strengthening powder according to the role played.

[0057] The original β grain boundary strengthening powder includes TiB2 powder and La powder (i.e. lanthanum powder), and the mass fraction of the original β grain boundary strengthening powder in the composite powder is 2.5%; the particle size of the original β grain boundary strengthening powder is 0.05-10 μm;

[0058] The α / β phase boundary strengthening powder includes Si powder, and the mass fraction of the α / β phase boundary strengthening powder in the composite powder is 0.05%; the particle size of the α / β phase boundary strengthening powder is 0.05-5 μm;

[0059] The matrix strengthening powder includes Mo powder, and the mass fraction of the matrix strengthening powder in the composite powder is 5%; the particle size of the matrix strengthening powder is 0.01-5 μm.

[0060] Step 2: Weigh TC25G alloy (also the matrix alloy) powder and the additional powder M according to the designed mass ratio, and mix them by ball milling to make the powders evenly mixed to obtain composite powder.

[0061] Among them, the nominal composition of the TC25G titanium alloy powder used is Ti-6.5Al-4Zr-2Sn-4Mo-1W-0.2Si, and the particle size of the TC25G alloy spherical powder is 10-300μm.

[0062] During the ball milling mixing, the rotation speed of the ball mill is 180 r / min, the ball milling time is 5 h, the ball-to-material ratio is 3:1, and the ball milling atmosphere is Ar gas.

[0063] Step 3: hot-pressing and sintering the obtained composite powder in a vacuum-sealed container, and performing an in-situ autogenous reaction to prepare a bulk composite material. The original β grain boundary, α / β phase interface, matrix composition and organization of the matrix alloy are enhanced by the in-situ autogenous reaction.

[0064] The added TiB2 powder generates TiB whiskers at the original β grain boundaries through an in-situ autogenous reaction. The TiB whiskers generated by the reaction are short rod-shaped or needle-shaped, with a length of 1-50μm and a width of 0.1-5μm. The TiB whiskers play a role in bearing loads and improve the strength of the material at room temperature and high temperature. At the same time, TiB, as a nucleation site for the α phase, can significantly refine the matrix grains, avoid the appearance of coarse Widmanstatten structure, and improve the strength and plasticity of the material.

[0065] The added La powder reacts with O at the original β grain boundary to generate a stable high melting point compound La2O3. The La2O3 generated by the reaction is in granular form with a size of 0.05-10μm. La2O3 is dispersed in the matrix alloy, playing a role of dispersion strengthening, which is beneficial to improving the high temperature instantaneous strength and endurance strength of the matrix alloy. In addition, the reduction of O content in the matrix and the interface solves the problem of powder metallurgy brittleness and improves the plasticity of the material.

[0066] The added Si powder generates at least one of the reinforcing phases (Ti, Zr) 5Si3 and (Ti, Zr) 6Si3 at the α / β phase interface through an in-situ autogenous reaction, and is distributed at the α and β phase interfaces. The reinforcement generated by the reaction is in the form of submicron particles with a size of 0.01-5μm. The dispersed silicide can bear the load and effectively hinder the dislocation movement, thereby improving the high temperature strength and creep resistance of the titanium alloy.

[0067] The strengthening of the matrix mainly comes from the effect of the added element Mo (i.e. strengthening element) on the material composition and structure. The added element Mo is dissolved in the matrix crystal at the atomic scale to exert a strengthening and toughening effect. This in turn improves the high-temperature softening resistance of the matrix titanium alloy. The effect on the composition refers to the high-melting-point Mo element being dissolved in the lattice, which on the one hand exerts the effect of solid solution strengthening, and on the other hand improves the stability of the material at high temperatures. The strengthening of the structure refers to the matrix with a multi-scale microstructure regulated by thermal deformation.

[0068] In the hot pressing sintering, the hot pressing sintering temperature is 1200° C., the hot pressing sintering pressure is 30 MPa, and the sintering time is 1 hour.

[0069] Step 4: hot-extrude the obtained bulk composite material to regulate the matrix structure, further refine the grains, and obtain a titanium-based composite material (also a multi-scale matrix structure) with excellent room temperature strength and plasticity and service performance above 700°C.

[0070] like Figure 4 As shown, the matrix structure is a basket-like structure formed by the α phase and the β phase. The α phase is lamellar, including a micron-sized primary α phase and a nanometer-sized secondary α phase, and the β phase is separated by the interwoven α phases. The primary α phase lamella length is 1-50 μm and the width is 0.5-3 μm; the secondary α phase lamella length is 0.05-2 μm and the width is 10-200 nm.

[0071] TiB whiskers are arranged linearly along the extrusion direction at the interface of the original matrix ball after deformation (i.e. after hot extrusion treatment), and are distributed in a network shape perpendicular to the extrusion direction. La2O3 particles are distributed at the interface of the original matrix ball after deformation (i.e. after hot extrusion treatment).

[0072] During hot extrusion, the block material is kept warm in a box-type heat treatment furnace for 30 minutes, the holding temperature is 1100°C, the extrusion die is kept warm at 400°C, and the extrusion ratio is 13:1.

[0073] like Figure 5 As shown in the figure, the titanium-based composite material with both room temperature strength, plasticity and serviceability prepared by the above steps has a room temperature tensile strength σ b is 1402MPa, the elongation δ is 10.6%, and the tensile strength σ at 700℃ b The tensile strength is 720 MPa and the elongation δ is 27%.

[0074] Embodiment three:

[0075] like Figure 1 As shown, in a specific embodiment of the present invention, a method for preparing a titanium-based composite material having both high strength and toughness and 700°C service performance comprises the following specific steps:

[0076] Step 1: According to the designed content of reinforcing phase or reinforcing element, the calculated mass ratio of TC25G alloy powder and additional powder M is as follows. The additional powder M is classified into original β grain boundary strengthening powder, α / β phase boundary strengthening powder and matrix strengthening powder according to the role played.

[0077] The original β grain boundary strengthening powder includes B powder (i.e., boron powder) and Y powder, and the mass fraction of the original β grain boundary strengthening powder in the composite powder is 0.05%; the particle size of the original β grain boundary strengthening powder is 0.05-10 μm;

[0078] The α / β phase boundary strengthening powder includes Si powder, and the mass fraction of the α / β phase boundary strengthening powder in the composite powder is 3%; the particle size of the α / β phase boundary strengthening powder is 0.05-5 μm;

[0079] The matrix strengthening powder includes Ta powder, and the mass fraction of the matrix strengthening powder in the composite powder is 2%; the particle size of the matrix strengthening powder is 0.01-5 μm.

[0080] Step 2: Weigh TC25G alloy (also the matrix alloy) powder and the added powder M according to the designed mass ratio, and mix them by ball milling to make the powders evenly mixed to obtain composite powder.

[0081] Among them, the nominal composition of the TC25G titanium alloy powder used is Ti-6.5Al-4Zr-2Sn-4Mo-1W-0.2Si, and the particle size of the TC25G alloy spherical powder is 10-300μm.

[0082] During the ball milling mixing, the rotation speed of the ball mill is 250 r / min, the ball milling time is 5 h, the ball-to-material ratio is 4:1, and the ball milling atmosphere is Ar gas.

[0083] Step 3: hot-pressing and sintering the obtained composite powder in a vacuum-sealed container, and performing an in-situ autogenous reaction to prepare a bulk composite material. The original β grain boundary, α / β phase interface, matrix composition and organization of the matrix alloy are enhanced by the in-situ autogenous reaction.

[0084] The added B powder generates TiB whiskers at the original β grain boundaries through an in-situ autogenous reaction. The TiB whiskers generated by the reaction are short rod-shaped or needle-shaped, with a length of 1-50 μm and a width of 0.1-5 μm. The TiB whiskers play a role in bearing loads and improve the strength of the material at room temperature and high temperature. At the same time, TiB, as a nucleation site for the α phase, can significantly refine the matrix grains, avoid the appearance of coarse Widmanstatten structure, and improve the strength and plasticity of the material.

[0085] The added Y powder reacts with O at the original β grain boundary to form a stable high melting point compound Y2O3. The Y2O3 generated by the reaction is in granular form with a size of 0.05-10μm. Y2O3 is dispersed in the matrix alloy, playing a role of dispersion strengthening, which is beneficial to improving the high temperature instantaneous strength and endurance strength of the matrix alloy. In addition, the reduction of O content in the matrix and the interface solves the problem of powder metallurgy brittleness and improves the plasticity of the material.

[0086] The added Si powder generates at least one of the reinforcing phases (Ti, Zr) 5Si3 and (Ti, Zr) 6Si3 at the α / β phase interface through an in-situ autogenous reaction, and is distributed at the α and β phase interfaces. The reinforcement generated by the reaction is in the form of submicron particles with a size of 0.01-5μm. The dispersed silicide can bear the load and effectively hinder the dislocation movement, thereby improving the high temperature strength and creep resistance of the titanium alloy.

[0087] The strengthening of the matrix mainly comes from the effect of the added element Ta (i.e., strengthening element) on the material composition and organization. The added element Ta is dissolved in the matrix crystal at the atomic scale to exert a strengthening and toughening effect, thereby improving the high-temperature softening resistance of the matrix titanium alloy. The effect on composition refers to the high-melting-point Ta element being dissolved in the lattice, which, on the one hand, exerts a solid solution strengthening effect, and on the other hand, improves the stability of the material at high temperatures. Organizational strengthening refers to the control of the matrix with a multi-scale microstructure through thermal deformation.

[0088] In the hot pressing sintering, the hot pressing sintering temperature is 1300° C., the hot pressing sintering pressure is 30 MPa, and the sintering time is 1 hour.

[0089] Step 4: hot-extrude the obtained bulk composite material to regulate the matrix structure, further refine the grains, and obtain a titanium-based composite material (also a multi-scale matrix structure) with excellent room temperature strength and plasticity and service performance above 700°C.

[0090] like Figure 6 As shown, the matrix structure is a basket-like structure formed by the α phase and the β phase. The α phase is lamellar, including a micron-sized primary α phase and a nanometer-sized secondary α phase, and the β phase is separated by the interwoven α phases. The primary α phase lamella length is 1-50 μm and the width is 0.5-3 μm; the secondary α phase lamella length is 0.05-2 μm and the width is 10-200 nm.

[0091] TiB whiskers are arranged linearly along the extrusion direction at the interface of the original matrix ball after deformation (i.e. after hot extrusion treatment), and are distributed in a network shape perpendicular to the extrusion direction. Y2O3 particles are distributed at the interface of the original matrix ball after deformation (i.e. after hot extrusion treatment).

[0092] During hot extrusion, the block material is kept warm in a box-type heat treatment furnace for 30 minutes, the holding temperature is 1000°C, the extrusion die is kept warm at 300°C, and the extrusion ratio is 17:1.

[0093] like Figure 7 As shown in the figure, the titanium-based composite material with both room temperature strength, plasticity and serviceability prepared by the above steps has a tensile strength σ at room temperature b 1449Mpa, elongation δ is 9.8%; tensile strength σ at 700℃ bIt is 744MPa and the elongation δ is 31%.

[0094] Table 1 below shows the mass fraction of the additional powder M (eg, original β grain boundary strengthening powder, α / β phase boundary strengthening powder and matrix strengthening powder) used in the preparation methods of Examples 1-3 in the composite powder.

[0095] Table 1

[0096]

[0097] The following Table 2 lists the additional powders M (eg, original β grain boundary strengthening powder, α / β phase boundary strengthening powder, and matrix strengthening powder) used in the preparation methods of Examples 1-3.

[0098] Table 2

[0099]

[0100] Table 3 below lists the performance parameters of the titanium-based composite material having both high strength and toughness and 700° C. service performance prepared by the preparation methods of Examples 1-3 at room temperature and 700° C.

[0101] Table 3

[0102]

[0103] like Figure 8 As shown, the results of three examples show that: the excellent comprehensive performance is room temperature tensile strength σ b Greater than 1300MPa, elongation δ greater than 8%. Tensile strength σ at 700℃ b Greater than 650MPa, and elongation δ greater than 20%.

[0104] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent replacement and improvement made to the above embodiments without departing from the content of the technical solution of the present invention, based on the technical essence of the present invention, within the spirit and principles of the present invention, still fall within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a titanium-based composite material having both high strength and toughness and 700°C service performance, characterized in that: The method for preparing a titanium-based composite material having both high strength and toughness and 700°C service performance comprises the following steps: Step 1: According to the designed content of the reinforcing phase, the content of the added original β grain boundary strengthening powder, the α / β phase boundary strengthening powder and the matrix strengthening powder in the raw material powder is calculated to determine the mass ratio of the TC25G alloy powder and each strengthening powder, wherein the original β grain boundary strengthening powder includes at least one of B powder, TiB2 powder, Y powder and La powder, with a particle size of 0.05-10 μm and a mass fraction of 0.05-5% in the composite powder, and the α / β phase boundary strengthening powder includes Si powder. , with a particle size of 0.05-5μm, at least one reinforcing phase of (Ti,Zr)5Si3 and (Ti,Zr)6Si3 is generated at the α / β phase interface, and the size of the reinforcing phase is 0.01-5μm, and the mass fraction of the α / β phase boundary reinforcing powder in the composite powder is 0.05-3%; the matrix reinforcing powder includes at least one of Ta powder, Mo powder and W powder, with a particle size of 0.01-5μm, and the mass fraction of the composite powder is 0.05-5%; Step 2: Weigh the TC25G alloy powder and the external powder according to the designed mass ratio, and mix them by ball milling to make the powders evenly mixed to obtain composite powder; Step 3, hot pressing and sintering the obtained composite powder, and performing an in-situ autogenous reaction to prepare a bulk composite material, and generating at least one reinforcing phase of TiB, Y2O3 and La2O3 at the original β grain boundary through the in-situ autogenous reaction; Step 4: hot-extrude the obtained bulk composite material to obtain a titanium-based composite material with both room temperature strong plasticity and serviceability. The matrix structure of the titanium-based composite material obtained by step 4 contains a dual-scale lamellar α phase, which is composed of a micron-scale primary α phase and a nanometer-scale secondary α phase. The β phase is separated by the interwoven α phase to form a basket-like structure. The primary α phase lamellae are 1-50 μm long and 0.5-3 μm wide; the secondary α phase lamellae are 0.05-2 μm long and 10-200 nm wide.

2. The method for preparing a titanium-based composite material having both high strength and toughness and 700°C service performance according to claim 1, characterized in that: The nominal composition of the TC25G alloy powder is Ti-6.5Al-4Zr-2Sn-4Mo-1W-0.2Si, and the particle size of the TC25G alloy spherical powder is 10-300 μm.

3. The method for preparing a titanium-based composite material having both high strength and toughness and 700°C service performance according to claim 1, characterized in that: The tensile strength σ of the titanium-based composite material obtained in step 4 at room temperature b Greater than 1300MPa, elongation δ greater than 8%; tensile strength σ at 700℃ b Greater than 650MPa, and elongation δ greater than 20%.

Citation Information

Patent Citations

  • Preparation method of multi-layer nano-particle reinforced high-toughness titanium-based composite material

    CN115821093A

  • W particle-TiB whisker hybrid reinforced titanium-based composite material and preparation method thereof

    CN116005084A

  • Reinforced phase oriented arrangement titanium-based composite material and preparation method thereof

    CN117535608A